Beauty products' hazard: realizing consumer rights in Malaysia - an overview / Hidhayatul Marikha Mohd Zuki and Nur Aslamiah Jamil - Mohd Zuki, Hidhayatul Marikha; Jamil, Nur Aslamiah (2006)
This project paper is about the various dangers posed by beauty products such as baby bath, deodorants, hygiene wash, hair dyes and antiageing products. It also covers on rights of consumers if they suffer any damage as consequences of using these beauty products. For ease of reference, this project paper is divided into five main chapters, dealing with the hazardous ingredients in beauty products, cosmetic regulations in Malaysia, the introduction, laws of other countries and finally, the conclusion and recommendation. The purpose of this project paper is to review the law regarding the beauty products which focuses on regulatory obligations and basis as a means and shield for the consumers of their rights, in the event of damages. Along the journey to complete this task, the result is surprising as the fact that in Malaysia, even to this date (2006) there is no specific regulation to govern the cosmetic industry, although this is one of the biggest industries in this country.1 Finally, it is hoped that those who read would benefit from this project paper.